2019
DOI: 10.1111/nrm.12229
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network‐based modeling of snow properties using field data and hyperspectral imagery

Abstract: This study attempts to model snow wetness and snow density of Himalayan snow cover using a combination of Hyperspectral image processing and Artificial Neural Network (ANN). Initially, a total of 300 spectral signature measurements, synchronized with snow wetness and snow density, were collected in the field. The spectral reflectance of snow was then modeled as a function of snow properties using ANN. Four snow wetness and three snow density models were developed. A strong correlation was observed in near‐infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Convolutional networks were inspired by early findings of biological processes; the connectivity pattern of CNN neurons resembles the organization of an animal's visual cortex. A CNN allows elements to be identified and classified with minimal pre-processing [32][33][34][35][36][37]. The CNNs are regularized multilayer perceptron variants.…”
Section: A Convolution Neural Networkmentioning
confidence: 99%
“…Convolutional networks were inspired by early findings of biological processes; the connectivity pattern of CNN neurons resembles the organization of an animal's visual cortex. A CNN allows elements to be identified and classified with minimal pre-processing [32][33][34][35][36][37]. The CNNs are regularized multilayer perceptron variants.…”
Section: A Convolution Neural Networkmentioning
confidence: 99%
“…The use of ML and DL has replaced other approaches in a variety of fields related to cryoshperic and natural hazard science, e.g., for the study of snow and glacial features (e.g., Haq et al, 2021b;a), snow cover mapping (e.g., Nijhawan et al, 2019), or to detect wet and dry snow (e.g., Tsai et al, 2019). Other approaches used ML to produce avalanche hazard maps that can be used for the prediction of future avalanche events (e.g., Rahmati et al, 2019) or to model snow wetness and snow density using artificial neural networks (e.g., Haq et al, 2019). Several scientific studies have demonstrated the potential of (semi-)automated avalanche detection from SAR (e.g., Vickers et al, 2016;2017;Wesselink et al, 2017;Abermann et al, 2019;Eckerstorfer et al, 2019;Leinss et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has proven its effectiveness in field, laboratory, and industrial applications [ 29 , 30 ]. Indeed, it has already been demonstrated that the near infrared (NIR) spectrum is sensitive to the physical parameters of snow [ 31 , 32 , 33 , 34 ]. In fact, snow granulometry is clearly visible in the NIR and the short waves of infrared regions (SWIR) [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%